Representasi Nilai-Nilai Islam dalam Film “Siksa Kubur” Melalui Analisis Wacana Foucauldian - Rio Febriannur Rachman (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study analyzes the Islamic values contained in the movie Siksa Kubur by Joko Anwar, which garnered four million viewers in theaters and was streamed on the OTT platform Netflix. The research adopts a qualitative approach using Foucauldian discourse analysis to explore the narrative and cinematic elements of the film as described by Himawan Pratista. The findings reveal that the film presents a discourse on Islamic values through visual and narrative representations of morality, the afterlife, and the relationship between knowledge and power. This discourse illustrates how religious values, such as the concepts of sin, punishment, and repentance, are internalized through cinematic elements such as dim lighting, eerie sound effects, and the symbolic depiction of Islamic culture. This study contributes to the body of Islamic media studies, particularly by uncovering the spiritual dimensions and the influence of religious discourse on the formation of subjectivity and moral identity in society.